(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
The article explores the theoretical and methodological foundations of organizing project-based natural science activities in primary school. Emphasis is placed on the significance of project-based learning for the development of young learners’ scientific competencies, research skills, environmental awareness, and critical thinking. The article focuses on a comprehensive study of the principles of organizing project-based learning in the natural science domain, their impact on student development, and the effectiveness of the educational process in primary school. An analysis of general didactic and subject-specific principles of organizing project-based natural science activities is conducted, including the principles of activity, natural conformity, visuality, integration, and instrumentality. Their role in structuring the educational process is examined, highlighting their contribution to engaging students in independent exploration of the environment, practical application of knowledge, and active problem-solving related to ecological issues. Specific subject-related principles that ensure the effective organization of project-based natural science activities are described. In particular, emphasis is placed on the local studies principle, which connects learning with the natural conditions, traditions, and historical-cultural heritage of the region. It is emphasized that these principles create optimal conditions for primary school students to develop research skills, critical thinking, and a value-based attitude toward nature. The study outlines prospects for further research aimed at improving methodologies for organizing project-based activities, which will contribute to the modernization of natural science education in primary school.